Korelasi antara Penguasaan Kosakata dengan Kemampuan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Zakia, Wilda; Halidjah, Siti; Salimi, Asmayani (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to determine the correlation between vocabulary mastery and the reading comprehension ability of class V Khuldi Islamic Elementary School students at Al-Azhar 21 Pontianak. The sample used was 20 students of class V Khuldi at Al-Azhar Islamic Elementary School 21 Pontianak using purposive sampling technique. The data collection technique used is a test technique using multiple choice questions to measure students' vocabulary mastery and students' reading comprehension abilities. Data analysis techniques carried out using statistical analysis with a significance level of 5% show the results that there is a correlation between vocabulary mastery and students' reading comprehension ability with r-value 0.985 > critical r-value 0.444. based on these data, it is concluded that there is a correlation between vocabulary mastery and students' reading comprehension abilities as the calculated r-value > critical r-value.